PENINGKATAN PEMAHAMAN FAKTA SEJARAH MELALUI METODE PEMBERIAN TUGAS PADA SISWA KELAS XI IPS 1 SMA ISLAM SULTAN AGUNG SEMARANG (Paramita: Historical Studies Journal, 2010)
Student learning achievement results on the subjects of History at SMA Islam Sultan Agung 1 Semarang still low. Therefore, there should be innovation and improvement of learning through the application of methods of assignment. Based on the results of this study concluded that through learning model with the method of giving the task, students' skills in presenting material in front of the classroom and independent study at home. Students become more confident at expressing opinions and to apply the science of history in public life. Variation application of this model can avoid the boredom of the students in following the history of learning so that student achievement has increased. After learning the method of giving the task of learning achievement of students increased 20.43% or 70.43% or 26 students. It turns out not as expected. So do the second cycle. And the result increased by 21.57% from the first cycle to 92% or about 34 students. Based on research that learning achievement IPS History student obtained a high school class XI IPS 1 Semarang Sultan Agung Islamic school year 2006/2007 the average value increased in the first cycle is 68 to around 80 on the second cycle. Key words: historical facts, recitation, learning history  Hasil prestasi belajar siswa pada mata pelajaran Sejarah di SMA Islam Sultan Agung 1 Semarang masih rendah. Oleh karena itu, harus ada inovasi dan peningkatan pembelajaran melalui penerapan metode penugasan. Berdasarkan hasil penelitian ini disimpulkan bahwa melalui model pembelajaran dengan metode pemberian tugas, kemampuan siswa dalam menyajikan materi di depan kelas dan belajar mandiri di rumah meningkat. Siswa menjadi lebih percaya diri pada pendapat menyatakan dan menerapkan ilmu sejarah dalam kehidupan publik. Variasi penerapan model ini dapat menghindari kebosanan siswa dalam mengikuti sejarah pembelajaran sehingga prestasi siswa meningkat. Setelah mempelajari metode pemberian tugas prestasi belajar siswa meningkat 20,43% atau 70,43% atau 26 siswa. Ternyata tidak seperti yang diharapkan. Begitu juga siklus kedua. Dan hasilnya meningkat sebesar 21,57% dari siklus pertama 92% atau sekitar 34 siswa. Berdasarkan penelitian bahwa prestasi belajar siswa yang diperoleh IPS Sejarah kelas sebuah sekolah tinggi XI IPS 1 Islam Sultan Agung Semarang tahun ajaran 2006/2007 nilai rata-rata meningkat pada siklus pertama adalah 68 untuk sekitar 80 pada siklus kedua.   Kata kunci: fakta-fakta sejarah, penugasa, belajar sejarah